2001
DOI: 10.1161/01.atv.21.6.1059
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Activity and Clinical Outcome in Unstable Coronary Artery Disease

Abstract: Abstract-In the current study, we investigated molecular markers of coagulation activity, ie, prothrombin fragment 1ϩ2 (F1ϩ2), thrombin-antithrombin (TAT) complex, soluble fibrin (SF), and D-dimer, and their relation to death, myocardial infarction, and refractory angina during and after anticoagulant treatment in unstable coronary artery disease. Patients with unstable coronary artery disease (Nϭ320) were randomized to a 72-hour infusion with either inogatran, a low-molecular-mass direct thrombin inhibitor, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
3
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 35 publications
1
43
3
7
Order By: Relevance
“…Hoffmeister et al [14] investigated the coagulation profile in UAP and demonstrated a persistently strong trend of elevated D-dimer levels during the first 10 days after admission. Accordingly, Oldgren et al [15] showed that on longterm follow-up (median 29 months) of patients with UAP, higher baseline levels of D-dimer were correlated with increased mortality. Although our study found that performance of the D-dimer ELISA at admission adds information on disease severity in this patient population, we did not assess the diagnostic value of the test for UAP.…”
Section: Discussionmentioning
confidence: 99%
“…Hoffmeister et al [14] investigated the coagulation profile in UAP and demonstrated a persistently strong trend of elevated D-dimer levels during the first 10 days after admission. Accordingly, Oldgren et al [15] showed that on longterm follow-up (median 29 months) of patients with UAP, higher baseline levels of D-dimer were correlated with increased mortality. Although our study found that performance of the D-dimer ELISA at admission adds information on disease severity in this patient population, we did not assess the diagnostic value of the test for UAP.…”
Section: Discussionmentioning
confidence: 99%
“…В ближайшие сутки после прекращения парен-терального введения препаратов гепарина у боль-ных с ОКСбпST описана реактивация заболевания, проявляющаяся как повышением в крови уровня лабораторных маркеров тромбообразования, так и возобновлением ишемии миокарда у части боль-ных [3][4][5][6][7]. При этом есть свидетельство, что после прекращения лечения антикоагулянтами у больных с достаточно низким риском неблагоприятного течения заболевания можно не опасаться возник-новения клинически выраженного феномена отмены.…”
Section: Early Discontinuation Of Fondaparinux In Low-risk Patients Hunclassified
“…В проведенных ранее исследованиях увеличение генерации тромбина (содержания в крови комплекса TAT и фрагмента протромбина 1+2), а также клини-ческие признаки возобновления ишемии миокарда отмечались вскоре после прекращения введения не фракционированного и низкомолекулярных гепа-ринов (далтепарина, эноксапарина) при преимуще-ственно неинвазивном лечении ОКСбпST [3][4][5][6][7][8]. Све-дений об активации тромбообразования после использования фондапаринукса найти не удалось, однако приведенные выше данные свидетельствуют в пользу наличия подобного феномена.…”
Section: изолированное увеличение показателейunclassified
See 1 more Smart Citation
“…[38] при наблюдении за больными с острым коронарным синдромом без подъема сегмента ST показали, что исходные уровни молекулярных маркеров коагуляционной активности (F1+2, фибрин, комплекс тромбин-антитромбин, D-димер) помогают выявлять пациентов с повышенной тромбогенной активностью. Длительное наблюдение (в среднем, в течение 29 мес) показало, что повы-шенный уровень D-димера связан с более высокой смертностью.…”
Section: D-димер плазмы и риск артериальных тромбозовunclassified